Etika Bisnis Syariah dalam Tata Kelola Fintech Perbankan Digital: Studi Kasus Bank Aladin Syariah - Neng Rosinawati (Journal of Economics, Management, and Accounting, 2026)
This study examines the role of Islamic business ethics in shaping fintech governance within digital Islamic banking, focusing on Bank Aladin Syariah as a case study. The rapid transformation of financial services through digitalization has created both opportunities and ethical challenges for Islamic banks, particularly in maintaining sharia compliance, transparency, and public trust. Using a qualitative case study approach based on secondary data from annual reports and prior empirical studies, this research analyzes how Islamic ethical values are integrated into governance structures, operational practices, and digital innovation. The findings indicate that Islamic business ethics function as a strategic foundation that strengthens Good Corporate Governance, enhances operational integrity, and supports sustainable performance. Ethical integration is reflected in transparent digital services, effective sharia supervision, improved financial performance indicators, and enhanced stakeholder trust. The study also reveals that ethical consistency contributes to institutional resilience amid regulatory changes and competitive pressures. Overall, the results emphasize that sustainable digital Islamic banking depends not only on technological advancement but also on the consistent implementation of Islamic ethical principles across governance, operations, and stakeholder relations